Prevention of fraud in procurement of goods and services based on e-procurement - Mansyuri, M. Ikhwan; Ramadhan, Muh. Syahru (Journal of Contemporary Accounting, 2024)
The government's practice of procuring goods and services is still vulnerable to fraud and needs to be addressed. This research aims to determine the factors that can influence efforts to prevent fraud in e-procurement-based procurement of goods and services. The data in this research were obtained from the results of distributing questionnaires to employees of the Procurement Services Unit (ULP) office and the Dompu Regency BPKAD Office. Sampling in this research used a purposive sampling method. Next, the research data was tested using multiple regression testing. This research can prove that the variables of technology utilization, internal control systems, employee ethics, and religiosity can influence the prevention of fraud in the procurement of goods and services. The research results can be used as a reference for evaluating the use of information technology and the application of SPI to make it more optimal. Apart from that, it is also necessary to consider human resources, in this case employees, to be able to maintain good ethics and religiosity as the basis for actions at work to avoid various deviant or unlawful actions.